The machine and dynamo: an analysis of liberalism as a meta-ideology applicable to revolutionary thought through the works “the discovery of freedom” and “the god of the machine” - Grego, Paulo; Marjorry Souza Santos, Suellen (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2024)
This article aims to broaden the concept of liberalism as a meta-ideology, presented by Scheffer (2023) to analyze the New Right, to the revolutionary ethos. This expansion will be based on the books "The discovery of freedom" by Rose Wilder Lade (1943) and "The god of the machine" by Isabel Paterson (1943). Furthermore, the French Revolution and the American Revolution were examined in order to provide comparative examples that distinguish the defense of liberty from the revolutionary ethos. Through this methodology, it was possible to identify a connection between the model of liberal society proposed by classical liberal thinkers and high trust societies, in which the revolutionary ethos proved incapable of reproducing and maintaining on its own.